Geographic Variation in Osteoporotic Hip Fracture Incidence: The Growing Importance of Asian Influences in Coming Decades - D. K. Dhanwal; C. Cooper; E. M. Dennison (Journal of Osteoporosis)
Studies over the last few decades have demonstrated geographic variation in the incidence of hip fracture across continents and among different parts of the same region. This paper studies the epidemiology of hip fracture worldwide, with special emphasis on the geographic variation among Asian countries. Using the Pubmed database, keywords that were employed included hip fracture, incidence rate, geographic variation, osteoporosis, and epidemiology. Articles were chosen based on the basis of (1) focus: studies that were said to specifically focus on geographic variation in hip fracture from different continents with a focus on Asia; (2) language: studies that were in English; (3) methods: studies that used statistical tests to examine hip fracture incidence rates. The highest hip fracture rates are seen in Scandinavian countries and the US and the lowest in African countries. Fracture rates are intermediate in Asian populations. Among different ethnic populations, the highest fracture rates are seen in Caucasians and the lowest in blacks. There is also a north-south gradient, particularly in Europe, where more hip fractures occur in North Europe compared to the South.